Preparation method of high-stability beta-carotene fortified potato powder

CN122997331APending Publication Date: 2026-10-30LUOHE YUDINGYUAN FOOD IND CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611152002.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的是针对背景技术中存在现有技术中β-胡萝卜素在土豆粉中分散性差、加工损失大、储存易氧化、影响产品品质的问题,提出一种高稳定性β-胡萝卜素强化土豆粉的制备方法

Benefits of technology

[0021]通过乳化预混和OSA马铃薯糊精纳米包埋,将脂溶性β-胡萝卜素转化为水分散性纳米颗粒,再经Pickering乳液在颗粒表面形成防护膜,显著降低高温挤压和干燥过程中的热氧化降解。在优选工艺下,β-胡萝卜素的总加工损失率≤15%,保留率≥85%,以初始添加量计。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997331A_ABST
    Figure CN122997331A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of potato powder preparation, and particularly relates to a preparation method of high-stability beta-carotene fortified potato powder. The technical scheme comprises the following steps: beta-carotene and glycerol monostearate are mixed at a mass ratio of 1:5, and stirring is carried out at 40-50 DEG C until uniformity is achieved to obtain a premixed oil phase; the premixed oil phase is added into an octenyl succinic anhydride esterified potato dextrin aqueous solution, and high-speed shearing and high-pressure homogenization treatment are sequentially carried out to form a nanoemulsion, and then spray drying is carried out to obtain beta-carotene nano-embedded powder; chitosan and aloe extract are compounded to prepare nanoparticles, which are dispersed in water. Through the synergistic effect of emulsification premixing, OSA dextrin nano-embedding, Pickering emulsion protection and low-temperature processing, the processing retention rate and storage stability of beta-carotene in potato powder are significantly improved, and the original taste and forming quality of the product are maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of potato starch preparation technology, and more particularly to a method for preparing highly stable β-carotene-fortified potato starch. Background Technology

[0002] Potato starch, a staple food product made from potato starch or potato flour, has a huge consumption volume. Adding β-carotene (a precursor to vitamin A) to potato starch can effectively improve public nutrition. However, β-carotene is a fat-soluble compound, exhibiting significant stability issues in the water-based starch system of potato starch: on the one hand, β-carotene is difficult to disperse evenly and easily aggregates to form discoloration spots; on the other hand, its molecule contains multiple conjugated double bonds, making it highly sensitive to heat, oxygen, and light. It is easily degraded during the high-temperature extrusion (typically >90℃) and hot-air drying (typically >70℃) processes in potato starch processing, resulting in a processing retention rate generally below 50%. Furthermore, the finished product suffers continuous loss due to oxidation and light exposure during room temperature storage, resulting in a short shelf life. Simply adding β-carotene or ordinary encapsulants can also damage the gel network structure of potato starch, affecting its texture, chewiness, and formability. Existing technologies mostly employ direct mixing or single encapsulation methods, which cannot simultaneously solve the four problems of dispersion, processing loss, storage stability, and quality maintenance, thus making it difficult to achieve efficient, stable, and industrially feasible application of β-carotene in potato starch.

[0003] Therefore, this application proposes a method for preparing highly stable β-carotene-fortified potato flour. Summary of the Invention

[0004] The purpose of this invention is to address the problems in the prior art where β-carotene has poor dispersibility in potato flour, large processing losses, easy oxidation during storage, and affects product quality, and to propose a method for preparing highly stable β-carotene-fortified potato flour.

[0005] The technical solution of this invention: A method for preparing highly stable β-carotene-fortified potato powder, comprising the following steps:

[0006] S1. Mix β-carotene and glyceryl monostearate at a mass ratio of 1:5 and stir at 40-50°C until homogeneous to obtain a premixed oil phase;

[0007] S2. The premixed oil phase is added to an aqueous solution of octenyl succinic anhydride esterified potato dextrin, and then subjected to high-speed shearing and high-pressure homogenization to form a nanoemulsion, followed by spray drying to obtain β-carotene nano-embedded powder.

[0008] S3. Chitosan and yucca extract are combined to prepare nanoparticles, which are dispersed in water. Then, β-carotene nanoparticles obtained in step S2 are added to form Pickering protective emulsion.

[0009] S4. Spray the Pickering protective emulsion obtained in step S3 evenly into the potato starch, mix evenly, and then extrude it at a temperature of ≤85℃.

[0010] S5. Dry the extruded material at a temperature of ≤60℃, cool it, and then sieve it.

[0011] S6. Highly stable β-carotene-fortified potato powder is obtained by using aluminum foil bags for light-proof and sealed packaging.

[0012] Optionally, in step S2, the mass concentration of the octenyl succinic anhydride esterified potato dextrin aqueous solution is 5% to 20%.

[0013] Optionally, in step S2, the pressure of the high-pressure homogenization is 50–150 MPa.

[0014] Optionally, in step S3, the mass ratio of chitosan to yucca extract is 1:1 to 5:1.

[0015] Optionally, in step S3, the average particle size of the nanoparticles is 100–500 nm.

[0016] Optionally, in step S4, the extrusion molding temperature is 80–85°C.

[0017] Optionally, in step S5, the drying is hot air drying or low-temperature vacuum dehydration; when low-temperature vacuum dehydration is used, the shelf life of the obtained product reaches 36 months.

[0018] Optionally, in step S4, vitamin C is added as a water-soluble antioxidant and sprayed into the potato starch along with the Pickering protective emulsion.

[0019] Optionally, in step S6, nitrogen gas is filled into the aluminum foil bag for protection.

[0020] Compared with the prior art, this application includes at least one of the following beneficial technical effects:

[0021] By premixing with emulsification and encapsulating with OSA potato dextrin nanoparticles, fat-soluble β-carotene is converted into water-dispersible nanoparticles. A protective film is then formed on the particle surface using a Pickering emulsion, significantly reducing thermal oxidative degradation during high-temperature extrusion and drying. Under the optimized process, the total processing loss of β-carotene is ≤15%, and the retention rate is ≥85%, based on the initial addition amount.

[0022] The aluminum foil bag's light-proof and airtight design, combined with a composite antioxidant system, effectively inhibits photo-oxidation and free radical chain reactions during storage. After 30 days of storage at room temperature away from light, the β-carotene retention rate is ≥80%. If low-temperature vacuum dehydration and nitrogen-filled packaging are used, the shelf life at room temperature can reach 36 months.

[0023] The encapsulation and protection system used in this invention requires a small amount of additive, which does not affect the gelatinization characteristics and gel network formation of potato starch. The resulting product has a natural appearance and color, a chewy texture, does not cloud the soup or break when cooked, and its forming stability is not significantly different from that of unfortified potato starch.

[0024] In summary, this invention significantly improves the processing retention rate and storage stability of β-carotene in potato starch through the synergistic effects of emulsification premixing, OSA dextrin nano-encapsulation, Pickering emulsion protection, and low-temperature processing, while maintaining the original taste and molding quality of the product. Attached Figure Description

[0025] Figure 1 This is a flowchart of a method for preparing highly stable β-carotene-fortified potato powder. Detailed Implementation

[0026] The present invention will be further described in detail below through specific embodiments and comparative examples. Unless otherwise specified, all raw materials used in the embodiments are food-grade and can be purchased from the market. The potato starch is a mixture of whole potato flour and potato starch in a 1:1 mass ratio. The purity of β-carotene is ≥96%. The processing retention rate and storage loss rate are determined by high performance liquid chromatography (HPLC) of the β-carotene content, calculated based on the initial addition amount. The dispersion uniformity is determined by visual inspection and colorimetry. Ten points are randomly selected, and a color difference ΔE < 3 is excellent, 3 ≤ ΔE < 6 is good, and ΔE ≥ 6 is poor. The taste and chewiness are scored by five trained sensory evaluators on a scale of 1-10, with 10 being the best, showing no difference from unfortified potato starch.

[0027] Example 1

[0028] like Figure 1 A method for preparing highly stable β-carotene-fortified potato powder includes the following steps:

[0029] (1) Pre-emulsification of β-carotene: Take 10g of β-carotene powder and 50g of glyceryl monostearate, i.e., a mass ratio of 1:5, place them in a constant temperature water bath, and stir at 200rpm for 20 minutes at 45℃ until a uniform orange-yellow oil phase premix is ​​formed.

[0030] (2) Nano-encapsulation: OSA potato dextrin was dissolved in deionized water with a degree of substitution of 0.05 to prepare 1000 mL of a 10% (w / w) OSA dextrin aqueous solution. The premixed oil phase from step (1) was slowly added to the aqueous solution, and simultaneously sheared at 12000 rpm for 2 minutes to form a primary emulsion. The primary emulsion was then homogenized twice under high pressure at 100 MPa to obtain a nanoemulsion with an average particle size of 180 nm. The nanoemulsion was spray-dried (inlet air temperature 175℃, outlet air temperature 85℃, feed rate 10 mL / min) to obtain β-carotene nano-encapsulated powder with an encapsulation rate of 91.5%.

[0031] (3) Preparation of Pickering protective emulsion: Weigh 5g of chitosan (90% deacetylation) and 2g of yucca extract (35% saponin content), dissolve them in 500mL of 0.5% acetic acid solution, and stir until completely dissolved. Under vigorous stirring, slowly add 100mL of 0.1% sodium tripolyphosphate solution, and continue stirring for 30 minutes to form a composite nanoparticle suspension. Centrifuge the suspension at 10000rpm for 15 minutes, discard the supernatant, wash the precipitate twice with deionized water, and redisperse it in 200mL of deionized water to obtain a composite nanoparticle aqueous dispersion. Dynamic light scattering measured the average particle size of the nanoparticles to be 215nm. Add 12g of β-carotene nano-embedded powder from step (2) to the dispersion, which is equivalent to a net β-carotene content of about 2.2g, and stir magnetically for 20 minutes to form a uniform and stable Pickering protective emulsion.

[0032] (4) Mixing and Low-Temperature Extrusion Molding: Take 10 kg of potato starch and place it in a three-dimensional mixer. Spray the Pickering protective emulsion from step (3) evenly into the potato starch using a high-pressure sprayer at a pressure of 0.3 MPa. Stir while spraying, and continue mixing for 8 minutes after spraying to ensure the emulsion fully coats the starch. The moisture content of the mixed material is 38.5%. A twin-screw extruder is used, with the temperature set at 75℃ for zone 1, 80℃ for zone 2, 83℃ for zone 3, and 85℃ for the die head. The screw speed is 120 rpm, and the material is extruded into round noodles with a diameter of 2.5 mm. The material stays in the extruder for about 1.5 minutes.

[0033] (5) Low-temperature drying: Spread the extruded vermicelli on a stainless steel mesh belt and place it in a hot air drying oven. The drying temperature is 60℃, the relative humidity is 40%, the wind speed is 1.5m / s, and the drying time is 90 minutes until the product moisture content is ≤12%. After taking it out, let it cool naturally to room temperature and use a vibrating screen to remove the debris.

[0034] (6) Sealing and stabilization treatment: Pack the product into aluminum foil bags at 200g / bag and seal them with a heat sealer (without nitrogen filling) to obtain highly stable β-carotene-fortified potato powder.

[0035] Example 2

[0036] (1) Pre-emulsification: Same as step (1) in Example 1.

[0037] (2) Nano-embedding: Same as step (2) in Example 1.

[0038] (3) Pickering protective emulsion: The mass ratio of chitosan to yucca extract was changed to 5:1, with 10g of chitosan and 2g of yucca extract. Other steps were the same as in Example 1 (3), and the average particle size of the nanoparticles was 198nm.

[0039] (4) Mixing powder and low-temperature extrusion molding: Mix the emulsion from step (3) with 2g of vitamin C (dissolved in 20mL of water) and spray it into 10kg of potato starch. Set the extrusion temperature to 70℃ in zone 1, 75℃ in zone 2, 78℃ in zone 3, and 80℃ at the die head. The rest is the same as step (4) in Example 1. The moisture content of the material is 37.2%.

[0040] (5) Low-temperature drying: Low-temperature vacuum dehydration is adopted. The extruded vermicelli is placed in a vacuum drying oven with a vacuum degree of -0.085MPa, a temperature of 50℃, and a drying time of 100 minutes until the moisture content is ≤12%.

[0041] (6) Sealing and stabilization treatment: After packaging in aluminum foil bags, vacuum and nitrogen filling are performed using a vacuum nitrogen-filling packaging machine to replace the residual oxygen until it is ≤1%, and then heat-sealed. The product is then obtained.

[0042] Example 3

[0043] (1) Pre-emulsification: The mass ratio of β-carotene to glyceryl monostearate is changed to 1:4, that is, 10g of β-carotene and 40g of glyceryl monostearate are mixed evenly at 45℃.

[0044] (2) Nano-encapsulation: The mass fraction concentration of OSA potato dextrin aqueous solution was changed to 5%. The high-speed shearing conditions remained unchanged, and the high-pressure homogenization pressure was changed to 50 MPa. The nano-encapsulated powder was obtained by spray drying, with an encapsulation rate of 85.2% and an average particle size of 320 nm.

[0045] (3) Pickering protective emulsion: the mass ratio of chitosan to yucca extract is 1:1, with 3g of chitosan and 3g of yucca extract. The average particle size of the prepared nanoparticles is 450nm. Other steps are the same as in Example 1 (3).

[0046] (4) Mixing powder and extrusion molding: The extrusion temperature is uniformly 85℃, and each section is 85℃. Other steps are the same as in Example 1, step (4).

[0047] (5) Drying: Same as step (5) in Example 1, dry with hot air at 60°C.

[0048] (6) Packaging: Same as step (6) in Example 1.

[0049] Example 4

[0050] (1) Pre-emulsification: β-carotene and glyceryl monostearate are mixed evenly at a mass ratio of 1:6, with 10g and 60g respectively.

[0051] (2) Nano-encapsulation: The concentration of OSA potato dextrin aqueous solution was 20%, the high pressure homogenization pressure was 150 MPa, and the other conditions were the same as in Example 1. The encapsulation rate of the encapsulated powder was 93.8%, and the average particle size was 125 nm.

[0052] (3) Pickering protective emulsion: chitosan to yucca extract mass ratio 3:1, chitosan 6g, yucca extract 2g, nanoparticle average particle size 280nm.

[0053] (4) Mixing powder and extrusion molding: The extrusion temperature is taken as the middle value of 82.5℃, and the temperature of each segment is 72.5℃, 77.5℃, 80℃ and 82.5℃ respectively.

[0054] (5) Drying: Low temperature vacuum dehydration is adopted, with a temperature of 40℃, a vacuum degree of -0.09MPa, and a time of 120 minutes.

[0055] (6) Packaging: Same as in Example 2, nitrogen-filled packaging.

[0056] Example 5

[0057] (1) Pre-emulsification: Same as in Example 1.

[0058] (2) Nano-encapsulation: OSA concentration 15%, homogenization pressure 100MPa, other conditions are the same as in Example 1, encapsulation rate 92.0%, average particle size 160nm.

[0059] (3) Pickering protective emulsion: chitosan to yucca extract mass ratio 2:1 (chitosan 4g, yucca extract 2g), nanoparticle average particle size 250nm.

[0060] (4) Mixing powder and extrusion molding: The extrusion temperature is 82℃, 72℃ in zone 1, 77℃ in zone 2, 79℃ in zone 3, and 82℃ at the die head.

[0061] (5) Drying: hot air drying temperature 55℃, humidity 40%, time 100 minutes.

[0062] (6) Packaging: Aluminum foil bags without nitrogen filling.

[0063] Comparative Example 1

[0064] (1) Mix 10g of β-carotene powder with 50g of glyceryl monostearate directly in a physical manner without heating or stirring until a uniform oil phase is obtained, resulting in a dry powder mixture.

[0065] (2) The dry powder mixture was mixed with a 10% (w / w) aqueous solution of OSA potato dextrin, and subjected to high-speed shearing, homogenization, and spray drying as in Example 1 to obtain the encapsulated powder. Due to the lack of pre-emulsification, the encapsulation rate was only 68.5%, and a large amount of free β-carotene crystals were present.

[0066] (3) Follow the same steps as in Example 1 (3)-(6). Note: Pickering emulsion still contains the embedding powder.

[0067] Comparative Example 2

[0068] (1) Pre-emulsification is the same as in Example 1.

[0069] (2) The premixed oil phase was added to 1000 mL of a 10% ordinary maltodextrin aqueous solution. The DE value of the maltodextrin was 15. The mixture was sheared, homogenized, and spray-dried as in Example 1. Most of the β-carotene in the resulting powder existed as micron-sized crystals, with an encapsulation rate of only 32%.

[0070] (3) The subsequent steps are the same as those in Example 1 (3)-(6).

[0071] Comparative Example 3

[0072] (1) and (2) are the same as in Example 1, and nano-embedded powder is obtained.

[0073] (3) Pickering emulsion is not prepared. 12g of the nano-embedded powder from step (2) is directly dispersed in 200mL of water without adding chitosan-yucca nanoparticles. The mixture is stirred into a suspension, which is unstable and easily settles.

[0074] (4) Spray the suspension into potato starch, and follow the same steps (4)-(6) as in Example 1.

[0075] Comparative Example 4

[0076] (1)-(3) are exactly the same as in Example 1.

[0077] (4) Extrusion temperature: Zone 1 85℃, Zone 2 90℃, Zone 3 93℃, Die head 95℃, other temperatures remain unchanged.

[0078] (5) Drying: Hot air drying temperature 80℃, humidity 40%, time 60 minutes.

[0079] (6) Packaging is the same as in Example 1.

[0080] Performance testing methods and results

[0081] Test items:

[0082] Processing retention rate (%) = β-carotene content in finished product / initial addition amount × 100%. The initial addition amount is calculated based on the β-carotene added in step (1), and is 10g for Examples 1-5 and Comparative Examples 1-4.

[0083] Loss rate (%) after 30 days of storage: After the product is stored at room temperature (25±2℃) and protected from light for 30 days, the β-carotene content is measured and calculated as (initial finished product content - content after 30 days) / initial finished product content × 100%.

[0084] Dispersion uniformity: Randomly select 10 points from the finished product, measure the L, a, and b values ​​using a colorimeter, calculate ΔE and compare it with the average value, and take the maximum ΔE as the rating.

[0085] Sensory evaluation (chewiness / texture): Take 20g of sample, boil it in boiling water for 5 minutes, take it out and rinse it with cold water, and have 5 evaluators score it independently from 1 to 10, and take the average value.

[0086] Results Table

[0087] Example 1 87.6 18.8 Excellent (ΔE=2.1) 9.2 Example 2 91.3 11.6 Excellent (ΔE=1.8) 9.5 Example 3 82.4 22.3 Good (ΔE=3.8) 8.7 Example 4 89.7 15.4 Excellent (ΔE=2.5) 9.1 Example 5 88.2 17.2 Excellent (ΔE=2.3) 9.3 Comparative Example 1 58.3 45.6 Difference (ΔE=8.2) 6.5 Comparative Example 2 41.7 52.8 Difference (ΔE=9.4) 5.8 Comparative Example 3 63.5 38.2 Good (ΔE=4.5) 7.9 Comparative Example 4 52.6 35.0 Good (ΔE=4.1) 7.2

[0088] Results and Conclusions: As shown in the table above, the processing retention rate of all embodiments of the present invention is ≥82.4%, significantly higher than that of any comparative example lacking core technical features. Example 2 achieved the highest retention rate of 91.3%. The loss rate after 30 days of storage was ≤22.3% for all embodiments, while it was ≥35.0% for the comparative examples, indicating the outstanding effect of the composite stabilizing system of the present invention.

[0089] Regarding dispersion uniformity, Examples 1, 2, 4, and 5 achieved "excellent" results, Example 3 achieved "good" results, while Comparative Examples 1 and 2 achieved "poor" results, indicating that emulsification premixing and OSA nano-encapsulation are crucial for uniform dispersion. In terms of sensory evaluation, the examples maintained scores between 8.7 and 9.5, significantly better than the comparative examples, especially Comparative Example 2, which had a poor taste, suggesting that OSA dextrin has a protective effect on the quality of potato starch.

[0090] Comparative Example 1 lacked pre-emulsification, Comparative Example 2 lacked OSA embedding, Comparative Example 3 lacked Pickering emulsion, and Comparative Example 4 employed high-temperature processing. The absence of any one of these technical features resulted in a significant decrease in retention rate, stability, uniformity, or sensory score, demonstrating a synergistic effect among the four core elements, none of which can be omitted. Although Example 3 used some extreme values ​​for its parameters, resulting in slightly lower performance than the optimal example, it was still significantly better than the comparative examples, indicating that the numerical range defined in this invention is reasonable and effective.

[0091] This invention utilizes emulsification premixing to form a homogeneous oil phase with glyceryl monostearate, eliminating the tendency of fat-soluble components to aggregate in the subsequent aqueous phase. OSA potato dextrin is then used for nano-encapsulation of the premixed oil phase, transforming β-carotene into water-dispersible particles that can be uniformly distributed throughout the potato flour, avoiding localized discoloration and uneven concentration. A Pickering emulsion constructed from chitosan and yucca extract nanoparticles forms a physical protective film on the surface of the β-carotene particles. This film resists direct contact with high temperatures and oxygen during extrusion molding and drying, reducing thermal degradation and oxidative losses. Controlling the extrusion temperature below 85°C and the drying temperature below 60°C further prevents the destruction of β-carotene caused by traditional high-temperature processing. These measures collectively ensure that β-carotene remains in a high proportion in the finished product after the entire processing flow, while preserving the starch gel network structure of the potato flour, maintaining the product's formability, elasticity, and texture consistent with unfortified potato flour.

[0092] The finished product is packaged in light-proof, sealed aluminum foil bags, cutting off the photo-oxidation pathway of β-carotene. Chitosan and yucca extract in the pickering emulsion possess antioxidant activity, continuously scavenging free radicals during storage and delaying the auto-oxidation of β-carotene. Vitamin C, as a water-soluble antioxidant, complements the fat-soluble β-carotene in the system, enhancing overall antioxidant capacity. Nitrogen purging further reduces the oxygen concentration within the packaging, inhibiting aerobic degradation reactions. These multi-layered stabilization measures ensure the product maintains its effective β-carotene content for a long time under normal temperature and light-proof conditions, preventing color fading and nutritional value decline due to nutrient loss. Simultaneously, due to the low amount of encapsulation and protection system added and its good compatibility with the starch matrix, the product does not exhibit off-flavors, cloudiness, or breakage during cooking and use, meeting consumer requirements for the appearance and taste of staple food products.

[0093] The above specific embodiments are merely several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant teachings of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

Claims

1. A method for preparing highly stable β-carotene-fortified potato flour, characterized in that, Includes the following steps: S1. Mix β-carotene and glyceryl monostearate at a mass ratio of 1:5 and stir at 40-50°C until homogeneous to obtain a premixed oil phase; S2. The premixed oil phase is added to an aqueous solution of octenyl succinic anhydride esterified potato dextrin, and then subjected to high-speed shearing and high-pressure homogenization to form a nanoemulsion, followed by spray drying to obtain β-carotene nano-embedded powder. S3. Chitosan and yucca extract are combined to prepare nanoparticles, which are dispersed in water. Then, β-carotene nanoparticles obtained in step S2 are added to form Pickering protective emulsion. S4. Spray the Pickering protective emulsion obtained in step S3 evenly into the potato starch, mix evenly, and then extrude it at a temperature of ≤85℃. S5. Dry the extruded material at a temperature of ≤60℃, cool it, and then sieve it. S6. Highly stable β-carotene-fortified potato powder is obtained by using aluminum foil bags for light-proof and sealed packaging.

2. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S2, the mass concentration of the octenyl succinic anhydride esterified potato dextrin aqueous solution is 5% to 20%.

3. The method for preparing highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S2, the pressure of the high-pressure homogenization is 50-150 MPa.

4. The method for preparing highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S3, the mass ratio of chitosan to yucca extract is 1:1 to 5:

1.

5. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S3, the average particle size of the nanoparticles is 100–500 nm.

6. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S4, the extrusion molding temperature is 80-85°C.

7. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S5, the drying is hot air drying or low-temperature vacuum dehydration; when low-temperature vacuum dehydration is used, the shelf life of the obtained product reaches 36 months.

8. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S4, vitamin C is added as a water-soluble antioxidant and sprayed into the potato starch along with the Pickering protective emulsion.

9. The method for preparing a highly stable β-carotene-fortified potato flour according to claim 1, characterized in that, In step S6, nitrogen gas is filled into the aluminum foil bag for protection.